From Morotai to Manus: The Australian War Crimes Trials of the Japanese, 1945-1951 and the Australian Legal Profession - Morris, Narrelle (Lawbook Co., 2019)
After World War II, Australia joined the Allied nations in responding to the allegations of shocking war crimes having been committed by the Axis Powers. In relation to the Pacific theatre of the war, Australia participated in the International Military Tribunal for the Far East held in Tokyo from 1946-48. Australian Military Courts also convened 300 war crimes trials of accused Japanese in various locations pursuant to the War Crimes Act 1945 (Cth). This article provides a brief overview of the legal framework and context of the military court trials. Many members of the Australian legal community served in the Australian Army Legal Corps during the war. After the war, some of them were posted to serve at the trials, as prosecuting and defending officers, as judges-advocate or reviewing officers and, very occasionally, as court members. This article briefly examines three prominent members of the Australian legal community who dealt with atrocities committed on Ambon: John Myles Williams (NSW), Alexander Davies Mackay (WA) and Kenneth Russell Townley (Qld). The military service of these and many other legal officers at the trials is not well known and much remains to be discovered about how their service intertwined with or affected their civilian legal or judicial careers.